How Career Choices are Influenced by Experience of Internship, Peer Group, and Interpersonal Skills? - Ana Awang, Devithania Putri; Fitriana Rahmawati; Robbani, Abdullah Azzam (Journal of Office Administration : Education and Practice, 2024)
This study was conducted to know the effect of Experience of Internship (X1), Peer group (X2), and Interpersonal Skills (X3) on Career Choices (Y). This research was conducted using a descriptive quantitative approach. Data collection was carried out by distributing questionnaires to students using Google Forms with a Likert scale, and this study used multiple regression analysis methods. The population in this study were undergraduate students of the Office Administration Education class of 2020 at Surabaya State University with a total of 63 people. This study used saturated sampling techniques in sampling. Based on the results of data analysis, it is found that Experience of Internship, Peer Group, and Interpersonal Skills have a positive and significant effect on Career Choices. This states that the Experience of Internship that a person has experienced and obtained, the group of friends that a person has, and a person's ability to communicate and interact with others provide influence and assistance in viewpoints on how career decisions will be in a person's life, especially in this case in line with research, namely in students.